Directed crystalline symmetry transformation of blue-phase liquid crystals by reverse electrostriction - Lin, Tsung-Hsien; Guo, Duan-Yi; Chen, Chun-Wei; Feng, Ting-Mao; Zeng, Wen-Xin; Chen, Po-Chang; Wu, Liang-Ying; Guo, Wen-Ming; Chang, Li-Min; Jau, Hung-Chang; Wang, Chun-Ta; Bunning, Timothy J.; et al. (Nature communications, 2024)
Soft-matter-based photonic crystals like blue-phase liquid crystals (BPLC) have potential applications in wide-ranging photonic and bio-chemical systems. To date, however, there are limitations in the fabrication of large monocrystalline BPLCs. Traditional crystal-growth process involves the transition from a high-temperature disordered phase to an ordered (blue) phase and is generally slow (takes hours) with limited achievable lattice structures, and efforts to improve molecular alignment through post-crystallization field application typically prove ineffective. Here we report a systematic study on the molecular self-assembly dynamics of BPLC starting from a highly ordered phase in which all molecules are unidirectionally aligned by a strong electric field. We have discovered that, near the high-temperature end of the blue phase, if the applied field strength is then switched to an intermediate level or simply turned off, large-area monocrystalline BPLCs of various symmetries (tetragonal, orthorhombic, cubic) can be formed in minutes. Subsequent temperature tuning of the single crystal at a fixed applied field allows access to different lattice parameters and the formation of never-before-seen monoclinic structures. The formed crystals remain stable upon field removal. The diversity of stable monocrystalline BPLCs with widely tunable crystalline symmetries, band structures, and optical dispersions will significantly improve and expand their application potentials. Soft-matter-based photonic crystals like blue-phase liquid crystals (BPLC) have potential applications but face fabrication limitations for large monocrystalline structures. The authors report a method to rapidly form large-area monocrystalline BPLCs with various symmetries and tunable properties through an application of electric fields and temperature control.